Proposed Exercises Using Flexible Resisters And Their Effect On Developing Strength Endurance And The Performance of Some Offensive Skills In Youth Basketball - Mohameed, Omer; Mohameed, Laith (Journal of Physical Education, 2017)
The importance of the research lies in using flexible resistors in developingstrength endurance and performing some offensive skills in basketball. The problem of theresearch lies in physical preparation was very poor during special preparation phase. Theresearchers used the experimental method. The subjects were (8) u18 basketball players fromthe national center for gifted in basketball season 2015 – 2016. The data was collected andtreated using proper statistical operation to conclude that physical training using flexibleresistors was more effective in developing physical performance and skill. Finally theyrecommended the necessity of dedicating time to develop the physical aspects as well astraining physical abilities using flexible resistors.